Coping strategies, quality of life and pain in women with breast cancer - Khalili, Narjes (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Breast cancer is the most common malignancy among Iranian women and is a significant stressor in women's life that may affect their coping strategies and quality of life. This study aimed to investigate coping strategies, quality of life and pain of women with breast cancer. MATERIALS AND METHODS: This was a cross-sectional study which held in Seyed-AL shohada hospital and two private offices in Isfahan, Iran. Target population was women with confirmed diagnosis of breast cancer in a recent year and between 18 and 60 years old. Data were collected via3 questionnaires (Brief cope, EORTC QLQ-C30 and Brief pain Inventory). The reliability and validity of these questionnaires were confirmed in different studies. Sixty-two patients completed the questionnaires. Analysis included descriptive statistics and Pearson correlation coefficient and t-test where necessary. All analysis were conducted using the SPSS version 16.0 and P-value of less than 0.05 considered as statistically significant. RESULTS: Sixty-two women with breast cancer completed questionnaires. The mean age of respondents was 45/81±6/78 years; most married (93/5%), high school-educated (41/97%), house wife (82/3%) and stage II (46/8%). The most common coping strategies were religion, acceptance, self-distraction, planning, active coping, positive reframing and denial. Mean score for the worst pain during the past 24 hours was 6/24 ± 2/55 and for the least pain was 3/19 ± 2/17. The global health scale was 60.34 ± 21.10. Emotion-focused coping strategies were positively and significantly related to symptom aspect of quality of life (r = 0/43 P ≤ 0/01) and affective interference of pain (r = 0/36 P = 0/004) and also was inversely correlated to functional health status (r = −0/38 P = 0/002). There was no significant correlation between problem-focused coping strategies and dimensions of quality of life and also different aspects of pain. CONCLUSIONS: The findings of this study indicated that the care of breast cancer should address physical, psychological and social wellbeing and the findings point to the importance of taking individual coping strategies into account when evaluating the impact of breast cancer on psychosocial wellbeing. Description of coping strategies might be useful for identifying patients in need to particular counseling and support.